Forage sources in total mixed rations on rumen fermentation, gut fill, and development of the gastrointestinal tract of dairy calves - Toledo, A. F.; Silva, A. P.; Barbosa, F. V.L.; Barboza, R. D.F.; Oliveira, I. C.R.; Marino, E. D.; Polizel, D. M. [UNESP]; Bittar, Carla M. M. (Springer Nature, 2024)
The inclusion of forage sources in calf diets is often discussed, and the main point debated is whether the inclusion level, particle size, source, and how forage is offered may impact gut fill and reduce body weight gain, as well as impact gastrointestinal tract development. This study aimed to determine the effects of feeding forage sources with different qualities on rumen fermentation, gut fill, and development of the gastrointestinal tract of dairy calves. Forty-eight Holstein dairy calves were blocked according to sex and body weight (BW) at 28 days of life and randomly assigned to 1 of 4 dietary treatments. Treatments consisted of a no-forage coarsely ground starter (CON) or total mixed rations containing 7.5% on DM basis of Tifton hay of either medium quality (MH) or low quality (LH) or 10% on DM basis of corn silage (CS). The nutritional content, including crude protein, NDF, lignin, and in vitro digestibility, was used as forage quality criteria. During the first 28 days of life, all calves received 3 L of whole milk twice daily, a commercial pelleted starter ad libitum, and no forage. After that, the solid diet was changed to the respective dietary treatments. Rumen samples were taken to determine rumen pH and volatile fatty acid (VFA) proportions. Calves were gradually weaned from 52 to 56 d of age, and 20 calves, 5 per treatment, were harvested two weeks after weaning. The anatomical parts of the gastrointestinal tract were weighed with and without contents, and histological analysis of rumen epithelium was conducted. The CON diet increased total VFA concentration compared to forage diets. The forage diets increased rumen pH, fecal pH, and gut fill. However, regardless of the source, the forage provision did not affect empty body weight. In addition, the forage provision increased the number of papillae in the rumen, but diets did not influence the length and width of papillae. The results suggest that 7.5% of Tifton hay, regardless of the quality, and 10% of corn silage in high-starch mixed diets benefit rumen health and promote greater gut fill without negative effects on final body weight.
Keywords: Dairy calves; Forage sources; Histological; Rumen fermentation; Tract filling